Electrophysiologic Correlates of Attention versus Stimulus Competition in Young Male and Female Listeners - Carpenter, Michael; De Chicchis, Albert R.; Cranford, Jerry L.; Hymel, Murvin R. (Journal of the American Academy of Audiology, 2001)
The effects of attention and stimulus competition on the late auditory-evoked potential (LAEP) were compared in 10 young males and 10 young females. Listeners attended to discrim- inably different oddball tonal sequences presented binaurally or monaurally. Peak amplitudes in response to the frequent tones were measured for Np P2, and early and late N2 (N2e and N2I) components of the LAEP. Whereas N, amplitudes increased, the amplitudes of P2 decreased when listeners attended to, rather than ignored, the tones. Competition effects for both N, and P2 resulted in reduced amplitudes in the presence of contralateral competition. Although findings with N2e and N2I suggested possible attention and competition effects, as well as gender differences, the data were inconsistent and will need further experimental verification. The present findings with the N1 and P2 components provide evidence that different neural processes underlie the attention and competition effects in the human brain.Abbreviations: EEG = electroencephalographic activity, ERP = event-related potential, LAEP = late auditory-evoked potential, PN = processing negativity, SOA = stimulus-onset asynchrony
Keywords: Attention; auditory event-related potential; competition; N1; N2; P2; processing negativity